2016
DOI: 10.1038/srep23670
|View full text |Cite
|
Sign up to set email alerts
|

Mutant GDF5 enhances ameloblast differentiation via accelerated BMP2-induced Smad1/5/8 phosphorylation

Abstract: Bone morphogenetic proteins (BMPs) regulate hard tissue formation, including bone and tooth. Growth differentiation factor 5 (GDF5), a known BMP, is expressed in cartilage and regulates chondrogenesis, and mutations have been shown to cause osteoarthritis. Notably, GDF5 is also expressed in periodontal ligament tissue; however, its role during tooth development is unclear. Here, we used cell culture and in vivo analyses to determine the role of GDF5 during tooth development. GDF5 and its associated BMP recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…For example, efficient primordial germ cell differentiation was shown to require a combination of both BMP4 and BMP8b homodimers, provoking the question of whether these ligands are integrated through balance detection (Ying et al, 2001). Conversely, BMP2 and BMP7 show opposing effects on ureter branching in developing kidneys (Piscione et al, 1997), suggesting they may operate in a ratiometric mode, and similar interactions were recently reported for BMP2 and GDF5 in multiple contexts (Klammert et al, 2015; Liu et al, 2016). The framework described here can be used to analyze these and other specific biological processes that utilize multiple BMPs (Açil et al, 2014; Bandyopadhyay et al, 2006; Chen et al, 2013).…”
Section: Discussionsupporting
confidence: 73%
“…For example, efficient primordial germ cell differentiation was shown to require a combination of both BMP4 and BMP8b homodimers, provoking the question of whether these ligands are integrated through balance detection (Ying et al, 2001). Conversely, BMP2 and BMP7 show opposing effects on ureter branching in developing kidneys (Piscione et al, 1997), suggesting they may operate in a ratiometric mode, and similar interactions were recently reported for BMP2 and GDF5 in multiple contexts (Klammert et al, 2015; Liu et al, 2016). The framework described here can be used to analyze these and other specific biological processes that utilize multiple BMPs (Açil et al, 2014; Bandyopadhyay et al, 2006; Chen et al, 2013).…”
Section: Discussionsupporting
confidence: 73%
“…GDF-5, also known as cartilage-derived morphogenetic protein-1 or BMP-14, is postnatally expressed in cells of the periodontal ligament, especially after initiation of enamel synthesis (Liu et al 2016). In this context, GDF-5 may act upstream of BMP-2, which then promotes ameloblast differentiation (Liu et al 2016), although the exact role of GDF-5 as an upstream "weak" activator of BMP-2 activity remains to be clarified.…”
Section: Tooth Developmentmentioning
confidence: 99%
“…GDF-5, also known as cartilage-derived morphogenetic protein-1 or BMP-14, is postnatally expressed in cells of the periodontal ligament, especially after initiation of enamel synthesis (Liu et al 2016). In this context, GDF-5 may act upstream of BMP-2, which then promotes ameloblast differentiation (Liu et al 2016), although the exact role of GDF-5 as an upstream "weak" activator of BMP-2 activity remains to be clarified. The importance of BMP signaling in tooth development is also underscored by tooth phenotype resulting from genetic mutations in the human GREM2 gene, which encodes "protein related to DAN and cerberus" (PRDC), and the corresponding phenotype of Grem2 2/2 mice with characteristic dental defects, including small and malformed incisors (Kantaputra et al 2015).…”
Section: Tooth Developmentmentioning
confidence: 99%
“…For a better understanding of the molecular mechanism during tooth development, we had previously identified several genes preferentially expressed in ameloblast lineage and had analyzed their roles in tooth development ( Saito et al, 2015 ; Liu J. et al, 2016 ; Miyazaki et al, 2016 ; Nakamura et al, 2016 ; Arai et al, 2017 ; Han et al, 2018 ; Nakamura et al, 2020 ). We had also identified novel genes from tooth germ complementary DNA library, namely Ameloblastin ( Ambn ), Epiprofin ( Epfn ), and AmeloD ( Dhamija et al, 1999 ; Nakamura et al, 2004 ; He et al, 2019 ), and each of these knockout mice models showed severe enamel hypoplasia ( Fukumoto et al, 2004 ; Nakamura et al, 2008 , 2017 ; Aurrekoetxea et al, 2016 ; Chiba et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%